PENGARUH KUALITAS AUDITOR, LIKUIDITAS, PROFIBILITAS DAN SOLVIBILITAS TERHADAP OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN PERIODE 2018-2022 - Nelsari_Malau, Yois; Hanssel Filbert; Kevin; Niarita Bukit (Journal Accounting International Mount Hope, 2024)
The aim of this study is to find out the impact of Auditor Quality, Liquidity, Profitability and Solvency on Audit Opinion Going Concerns on Food and Beverage Sub-Sector Manufacturing Companies Period 2018-2022. The research will be carried out by the food and beverage companies that are listed on the Indonesian stock exchange through the website www.idx.co.id. This approach uses a quantitative approach, which is a method based on positivism that is used to study the population of a particular sample. The population to be used in this research is the number of consumer companies that are listed on the Indonesian stock exchange since the year 2018 until the year 2022. The number of people in this research is the total of 18 companies. The results of this study show that there is no partially significant influence between the Quality of Auditors on the Opinion of the Audit Going Concern. There is no Partially Significant Effect between the Liquidity on the Opportunity to Audit.